(untitled) (Revista Brasileira de Pesquisa em Educação em Ciências, 2011)
This paper deals with the relationships between classroom and students’ acquisitions. Firstly, we analyse the approaches taken by most of these studies where causality is established between the classrooms, viewed as opportunities to learn and the students’ performances. Then we present our approach based on the didactic theory of joint actions of teaching and learning and the associated methodology. This approach is illustrated drawing on the comparison of two physics classrooms (grade 10) during a physics teaching mechanics sequence. Relationships between these classroom practices and the students’ performances are established. In conclusion the comparison between the didactic approach and the others shows that the main difference is on the way of viewing classroom teaching: it is focused on the evolution of the classroom group over time from the perspective of the meaning c onstruction of the taught topic more than on classroom situations considered as a learning environments during a session.